PELATIHAN MANAJEMEN SENI PADA SANGGAR CITRA KARA DI DESA BATUAN, KECAMATAN SUKAWATI, BALI - Suardana, I Wayan; Ruastiti, Ni Made; Ruta, I Made; Suryantari, Eka Putri; Prasiasa, Dewa Putu Oka; Muka, I Ketut; Ardika, I Gusti Ngurah Putu (LP2M STP Mataram, 2024)
Arts management training at the Citra Kara aims to increase the practical benefits of crafts activities. Dominant kriyawan are skilled at leather crafts. However, quite a few kriyawan from the Cita Kara admit that their craft works could be more helpful. The problems : 1) What is the form of arts management training?; 2) How does arts management training impact?. The training uses R&D methods. The results : 1) training in selecting commodity materials, training in the production of commodities, technical assistance in the production of commodities, technical assistance in the coloring of commodities, training in the marketing of commodities, training in digital marketing and assistance in the digitalization of marketing of commodities; 2) there is an increase in artists' skills in producing new types of craft art commodities & there is an increase in artists' interest in marketing leather inlaid art commodities in new ways.